ANALISIS KEPUASAN NASABAH ATAS PEMBIAYAAN BNI FLEKSI SYARIAH PADA PT. BANK BNI SYARIAH TANJUNGKARANG - Suwandi -; Soewito - (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2019)
PT. BNI of Fleksi Syariah Tanjungkarang represent financial institution with Moslem lawprinciple which born as one of the alternative financial institution form to fulfill certain societysegmentation which is viewer that bank flower represent collision to syariat Islam. The main objective ofthis research to know level satisfaction of client defrayal BNI Fleksi Syariah at PT. BNI of Fleksi SyariahTanjungkarang.Factors which influencing satisfaction of client PT. BNI of Fleksi Syariah which its handlingrequire to be given high priority by company because existence of assessed this factor of vitalimportance by client, but management not yet executed him according to desire of customerFactors or variable influencing satisfaction of client of PT. BNI Fleksi Syariah which need to bedefended, because in general mount its execution have as according to client expectation andimportance, so that can gratify client. Factors or variable influencing satisfaction of client of PT. BNI ofFleksi Syariah still assumed by less important its influence to customer, its executor by run of the millcompany. Implication in improving service system at PT. Bank of BNI Fleksi Syariah Tanjungkarangshall perform a training and education to entire/all its employees especially to increase ability ofemployees in the case of: Comments handle sigh of customer and ability comprehend desire ofcustomer.